Automata, Languages and Programming, 37th International Colloquium, ICALP 2010, Bordeaux, France, July 6-10, 2010, Proceedings, Part I.

Towards a Systematic Approach for Capturing Knowledge-Intensive Business Processes - Trier, Matthias; Müller, Claudia (Practical Aspects of Knowledge Management)

Complexity and Approximation of a Geometric Local Robot Assignment Problem - Bonorden, Olaf; Degener, Bastian; Kempkes, Barbara; Pietrzyk, Peter (Algorithmic Aspects of Wireless Sensor Networks)
We introduce a geometric multi-robot assignment problem. Robots positioned in a Euclidean space have to be assigned to treasures in such a way that their joint strength is sufficient to unearth a treasure with a given weight. The robots have a limited range and thus can only be assigned to treasures in their proximity. The objective is to unearth as many treasures as possible. We investigate the complexity of several variants of this problem and show whether they are in $\classP$ or are $\classNP$-complete. Furthermore, we provide a distributed and local constant-factor approximation algorithm using constant-factor resource augmentation for the two-dimensional setting with $\bigO(\log^*n)$ communication rounds.

Reinforcement Learning for Blackjack - Kakvi, Saqib (Lecture Notes in Computer Science)

Three-Valued Spotlight Abstractions - Schrieb, Jonas; Wehrheim, Heike; Wonisch, Daniel (FM 2009: Formal Methods)

On Stackelberg Pricing with Computationally Bounded Consumers - Briest, Patrick; Hoefer, Martin; Gualà, Luciano; Ventre, Carmine (Lecture Notes in Computer Science)
In a Stackelberg pricing game a leader aims to set prices on a subset of a given collection of items, such as to maximize her revenue from a follower purchasing a feasible subset of the items. We focus on the case of computationally bounded followers who cannot optimize exactly over the range of all feasible subsets, but apply some publicly known algorithm to determine the set of items to purchase. This corresponds to general multi-dimensional pricing assuming that consumers cannot optimize over the full domain of their valuation functions but still aim to act rationally to the best of their ability. We consider two versions of this novel type of Stackelberg pricing games. Assuming that items are weighted objects and the follower seeks to purchase a min-cost selection of objects of some minimum weight (the Min-Knapsack problem) and uses a simple greedy 2-approximate algorithm, we show how an extension of the known single-price algorithm can be used to derive a polynomial-time (2 + ε)-approximation algorithm for the leader’s revenue maximization problem based on so-called near-uniform price assignments. We also prove the problem to be strongly NP-hard. Considering the case that items are subsets of some ground set which the follower seeks to cover (the Set-Cover problem) via a standard primal-dual approach, we prove that near-uniform price assignments fail to yield a good approximation guarantee. However, in the special case of elements with frequency 2 (the Vertex-Cover problem) it turns out that exact revenue maximization can be done in polynomial-time. This stands in sharp contrast to the fact that revenue maximization becomes APX-hard already for elements with frequency 3.

Creating Butterflies in the Core – A Network Coding Extension for MPLS/RSVP-TE - Biermann, Thorsten; Schwabe, Arne; Karl, Holger (NETWORKING 2009)

Reinforcement Learning for Blackjack - Kakvi, Saqib (Lecture Notes in Computer Science)

Uniform Budgets and the Envy-Free Pricing Problem - Briest, Patrick (Proceedings of the 35th InternationalColloquium on Automata, Languages and Programming (ICALP))

The Kinetic Facility Location Problem - Degener, Bastian; Gehweiler, Joachim; Lammersen, Christiane (Proceedings of the 11th Scandinavian Workshop on Algorithm Theory (SWAT))

Aggregating Robots Compute: An Adaptive Heuristic for the Euclidean Steiner Tree Problem - Hamann, Heiko; Wörn, Heinz (The tenth International Conference on Simulation of Adaptive Behavior (SAB'08))

On Faster Integer Calculations Using Non-arithmetic Primitives - Lürwer-Brüggemeier, Katharina; Ziegler, Martin (Unconventional Computing)

The k-Resource Problem on Uniform and on Uniformly Decomposable Metric Spaces - Bienkowski, Marcin; Kutyłowski, Jarosław (Lecture Notes in Computer Science)
We define a natural generalization of the prominent k-server problem, the k-resource problem. It occurs in metric spaces with some demands and resources given at its points. The demands may vary with time, but the total demand may never exceed k. The goal of an online algorithm is to satisfy demands by moving resources, while minimizing the cost for transporting resources. We give an asymptotically optimal O(log(min {n,k}))-competitive randomized algorithm and an O(min {k,n})-competitive deterministic one for the k-resource problem on uniform metric spaces consisting of n points. This extends known results for paging to the more general setting of k-resource. Basing on the results for uniform metric spaces, we develop a randomized algorithm solving the k-resource and the k-server problem on metric spaces which can be decomposed into components far away from each other. The algorithm achieves a competitive ratio of O(log(min {n,k})), provided that it has some extra resources more than the optimal algorithm.

Cryptanalysis of Unbalanced RSA with Small CRT-Exponent - May, Alexander (Advances in Cryptology — CRYPTO 2002)

Low Secret Exponent RSA Revisited - Blömer, Johannes; May, Alexander (Lecture Notes in Computer Science)

Key Revocation with Interval Cover Families - Blömer, Johannes; May, Alexander (Selected Areas in Cryptography)

Dimension Reduction Methods for Convolution Modular Lattices - May, Alexander; Silverman, Joseph H. (Lecture Notes in Computer Science)

A Probabilistic Zero-Test for Expressions Involving Roots of Rational Numbers - Blömer, Johannes (Algorithms — ESA’ 98)

Competitive Maintenance of Minimum Spanning Trees in Dynamic Graphs - Dynia, Miroslaw; Korzeniowski, Miroslaw; Kutyłowski, Jarosław (Proc. of the 33rd International Conference on Current Trends in Theory and Practice of Computer Science (SOFSEM'07))

(Short) Survey of Real Hypercomputation - Ziegler, Martin (Lecture Notes in Computer Science)

Real Computational Universality: The Word Problem for a Class of Groups with Infinite Presentation - Meer, Klaus; Ziegler, Martin (Mathematical Foundations of Computer Science 2007)

Upper Bounds on the Bisection Width of 3- and 4-Regular Graphs - Monien, Burkhard; Preis, Robert (Mathematical Foundations of Computer Science 2001)

Evaluating XPath Queries on XML Data Streams - Böttcher, Stefan; Steinmetz, Rita (Data Management. Data, Data Everywhere, 24th British National Conference on Databases, BNCOD 24)

Data Management for Mobile Ajax Web 2.0 Applications - Böttcher, Stefan; Steinmetz, Rita (Database and Expert Systems Applications, 18th International Conference, DEXA 2007)

Online Multi-path Routing in a Maze - Rührup, Stefan; Schindelhauer, Christian (Proc. of the 17th International Symposium on Algorithms and Computation (ISAAC 2006))

Reliable Broadcasting Without Collision Detection - Kutyłowski, Jarosław; Zagórski, Filip (SOFSEM 2006: Theory and Practice of Computer Science)
We propose a dynamic, ad-hoc communication network consisting of mobile units that can warn about traffic jams on motorways. Our goal is to provide a practical, low cost solution. Therefore we consider very simple wireless communication hardware, without collision detection, with very small bandwidth and a probabilistic model of link failure. We provide a complete system architecture. For this purpose we design and analyze solutions for size approximation, leader election and broadcasting. Our algorithms are fine-tuned for fast operation in a practical setting. We provide both a theoretical and experimental evaluation of our solutions. Our contribution is much different from the previous work, where either pure theoretical models with a pure theoretical analysis are provided or algorithms working in practical models are evaluated only through simulations.

Fault Based Collision Attacks on AES - Blömer, Johannes; Krummel, Volker (Lecture Notes in Computer Science)

Wagner’s Attack on a Secure CRT-RSA Algorithm Reconsidered - Blömer, Johannes; Otto, Martin (Lecture Notes in Computer Science)

Sign Change Fault Attacks on Elliptic Curve Cryptosystems - Blömer, Johannes; Otto, Martin; Seifert, Jean-Pierre (Lecture Notes in Computer Science)

Power-Aware Collective Tree Exploration - Dynia, Miroslaw; Korzeniowski, Miroslaw; Schindelhauer, Christian (Architecture of Computing Systems - ARCS)

Uncomputability Below the Real Halting Problem - Meer, Klaus; Ziegler, Martin (Logical Approaches to Computational Barriers)

De Dictionariis Dynamicis Pauco Spatio Utentibus ({lat.} On Dynamic Dictionaries Using Little Space) - Demaine, Erik D.; Meyer auf der Heide, Friedhelm; Pagh, Rasmus; Pǎtraşcu, Mihai (LATIN 2006: Theoretical Informatics)

Smart Robot Teams Exploring Sparse Trees - Dynia, M.; Kutyłowski, J.; Meyer auf der Heide, Friedhelm; Schindelhauer, Christian (Lecture Notes in Computer Science)

DTD-Driven Structure Preserving XML Compression - Böttcher, Stefan; Steinmetz, Rita (Flexible and Efficient Information Handling, 23rd British National Conference on Databases, BNCOD 23)

Information Disclosure by XPath Queries - Böttcher, Stefan; Steinmetz, Rita (Secure Data Management, Third VLDB Workshop, SDM 2006)

Cohen–Lenstra Heuristics of Quadratic Number Fields - Fouvry, Étienne; Klüners, Jürgen (Lecture Notes in Computer Science)
We establish a link between some heuristic asymptotic formulas (due to Cohen and Lenstra) concerning the moments of the p–part of the class groups of quadratic fields and formulas giving the frequency of the values of the p–rank of these class groups.

A Simpler Sieving Device: Combining ECM and TWIRL - Geiselmann, Willi; Januszewski, Fabian; Köpfer, Hubert; Pelzl, Jan; Steinwandt, Rainer (Information Security and Cryptology – ICISC 2006)

Performance Analysis of the Hierarchical Layer Graph for Wireless Networks - Rührup, Stefan; Schindelhauer, Christian; Volbert, Klaus (Proc. of 4th International Conference on Ad-Hoc, Mobile & Wireless Networks (ADHOC-NOW 2005))
The Hierarchical Layer Graph (HL graph) is a promising network topology for wireless networks with variable transmission ranges. It was introduced and analyzed by Meyer auf der Heide et al. 2004. In this paper we present a distributed, localized and resource-efficient algorithm for constructing this graph. The qualtiy of the HL graph depends on the domination radius and the publication radius, which affect the amount of interference in the network. These parameters also determine whether the HL graph is a c-spanner, which implies an energy-efficient topology. We investigate the performance on randomly distributed node sets and show that the restrictions on these parameters derived from a worst case analysis are not so tight using realistic settings. Here, we present the results of our extensive experimental evaluation, measuring congestion, dilation and energy. Congestion includes the load that is induced by interfering edges. We distinguish between congestion and realistic congestion where we also take the signal-to-interference ratio into account. Our experiments show that the HL graph contains energy-efficient paths as well as paths with a few number of hops while preserving a low congestion.

Probability Distributions for Channel Utilisation - Schindelhauer, Christian; Voß, Kerstin (Proc. of 4th International Conference on Ad-Hoc Networks & Wireless (ADHOC-NOW 2005))

Content Distribution in Heterogenous Video-on-Demand P2P Networks with ARIMA Forecasts - Loeser, Chris; Schomaker, Gunnar; Brinkmann, André; Vodisek, Mario; Heidebuer, Michael (Proceedings of the 4th International Conference on Networking)

A Tool Kit for Finding Small Roots of Bivariate Polynomials over the Integers - Blömer, Johannes; May, Alexander (EUROCRYPT 2005)

Partial Key Exposure Attacks on RSA up to Full Size Exponents - Ernst, Matthias; Jochemsz, Ellen; May, Alexander; de Weger, Benne (EUROCRYPT 2005)

Online Routing in Faulty Meshes with Sub-linear Comparative Time and Traffic Ratio - Rührup, Stefan; Schindelhauer, Christian (Algorithms – ESA 2005)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Facility Location in Sublinear Time - Bădoiu, Mihai; Czumaj, Artur; Indyk, Piotr; Sohler, Christian (Proc. of the 32nd International Colloquium on Automata, Languages and Programming (ICALP))

Online Occlusion Culling - Frahling, Gereon; Krokowski, Jens (Proc. of the 13th Annual European Symposium on Algorithms (ESA 2005))
Modern computer graphics systems are able to render sophisticated 3D szenes consisting of millions of polygons. In this paper we address the problem of occlusion culling. Aila, Miettinen, and Nordlund suggested to implement a FIFO buffer on graphics cards which is able to delay the polygons before drawing them. When one of the polygons within the buffer is occluded or masked by another polygon arriving later from the application, the rendering engine can drop the occluded one without rendering, saving important rendering time. We introduce a theoretical online model to analyse these problems in theory using competitive analysis. For different cost measures addressed we invent the first competitive algorithms for online occlusion culling. Our implementation shows that these algorithms outperform known ones for real 3D scenes as well.

Dynamic Page Migration Under Brownian Motion - Bienkowski, Marcin; Korzeniowski, Miroslaw (Proc. of the European Conference in Parallel Processing (Euro-Par))
We consider Dynamic Page Migration (DPM) problem, one of the fundamental subproblems of data management in dynamically changing networks. We investigate a hybrid scenario, where access patterns to the shared object are dictated by an adversary, and each processor performs a random walk in X. We extend the previous results of [4]: we develop algorithms for the case where X is a ring, and prove that with high probability they achieve a competitive ratio of O~(min{D−−√4,n}), where D is the size of the shared object and n is the number of nodes in the network. These results hold also for any d-dimensional torus or mesh with diameter at least Ω~(D−−√).

Bucket Game with Applications to Set Multicover and Dynamic Page Migration - Bienkowski, Marcin; Byrka, Jarosław (Proc. of the 13th Annual European Symposium on Algorithms (ESA 2005))
We present a simple two-person Bucket Game, based on throwing balls into buckets, and we discuss possible players' strategies. We use these strategies to create an approximation algorithm for a generalization of the well known Set Cover problem, where we need to cover each element by at least $k$ sets. Furthermore, we apply these strategies to construct a randomized algorithm for Dynamic Page Migration problem achieving the optimal competitive ratio against an oblivious adversary.

Cube Connected Cycles Based Bluetooth Scatternet Formation - Bienkowski, Marcin; Brinkmann, André; Korzeniowski, Miroslaw; Orhan, Orhan (Proceedings of the 4th International Conference on Networking)
Bluetooth is a wireless communication standard developed for personal area networks (PAN) that gained popularity in the last years. It was designed to connect a few devices together, however nowadays there is a need to build larger networks. Construction and maintenance algorithms have great effect on performance of the network. We present an algorithm based on Cube Connected Cycles (CCC) topology and show how to maintain the network so that it is easily scalable. Our design guarantees good properties such as constant degree and logarithmic dilation. Besides, the construction costs are proven to be at most constant times larger than any other algorithm would need.

Improved Algorithms for Dynamic Page Migration - Bienkowski, Marcin; Dynia, Miroslaw; Korzeniowski, Miroslaw (Proc. of the 22nd Symposium on Theoretical Aspects of Computer Science (STACS))
The dynamic page migration problem citedynamic-page-migration is defined in a distributed network of $n$ mobile nodes sharing one indivisible memory page of size $D$. During runtime, the nodes can both access a unit of data from the page and move with a constant speed, thus changing the costs of communication. The problem is to compute online a schedule of page movements to minimize the total communication cost. In this paper we construct and analyze the first deterministic algorithm for this problem. We prove that it achieves an (up to a constant factor) optimal competitive ratio $O(n cdot sqrtD)$. We show that the randomization of this algorithm improves this ratio to $O(sqrtD cdot log n)$ (against an oblivious adversary). This substantially improves an $O(n cdot sqrtD)$ upper bound from citedynamic-page-migration. We also give an almost matching lower bound of $Omega(sqrtD cdot sqrtlog n)$ for this problem.